Media freedom in Liberal thought: between theoretical visions and media practice - سعيدي, زينب (Milev Journal of Research and Studies, 2023)
Research into the concept of media freedom in terms of its scope, indicators and means of achieving it is still among the issues and problems that attract the interest of researchers and professionals alike, as the latter remains a relative meaning that varies according to historical development, and the accompanying intellectual, philosophical, social and political contexts, and according to the different ideologies and doctrine, Liberal thought has been interested in defining the concept of freedom and the justifications for its existence embodied in both the liberal theory and the social responsibility theory in the media, In this context, the current article will try to trace the development stages of this concept and the justifications for its existence, by referring to the historical contexts accompanying it, in addition to taking a critical approach to the reality of actual practice as the main test to judge the existence of this freedom or not. It was finally concluded that media freedom remained limited at the application level in liberal thought in light of the gap that theoretical ideas knew about media practice, despite the fundamental detailed transformation that media freedom has known from being an objective under liberal theory to being a means under the theory of social responsibility.